Decarboxylative ring-opening of 2-oxazolidinones: a facile and modular synthesis of β-chalcogen amines. Issue 53 (30th November 2022) - Galetto, Fábio Z.; da Silva, Cleiton; Beche, Ricardo I. M.; Balaguez, Renata A.; Franco, Marcelo S.; de Assis, Francisco F.; Frizon, Tiago E. A.; Su, Xiao
Abstract : This study includes a new protocol for the synthesis of primary and secondary β-chalcogen amines (Se, Te and S) from the ring-opening reaction of non-activated 2-oxazolidinones with chalcogenolate anions. Abstract : We report herein the synthesis of primary and secondary β-chalcogen amines through the regioselective ring-opening reaction of non-activated 2-oxazolidinones promoted by in situ generated chalcogenolate anions. The developed one-step protocol enabled the preparation of β-selenoamines, β-telluroamines and β-thioamines with appreciable structural diversity and in yields of up to 95%.